2015
DOI: 10.1016/j.ijsu.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Spleen hydatidosis treated by hemi-splenectomy: A low-morbidity, cost-effective management by a recently improved surgical technique

Abstract: Partial splenectomy for hydatidosis is effective and safe. Physicians and surgeons should be aware of such an easy-to-catch option when dealing with benign splenic conditions, such as parasitic cysts. Cost-effectiveness, low morbidity and the possible prevention of splenectomy-related infectious complications should plead in favor of this technique in developing countries, where hydatidosis is endemic and post-splenectomy drugs and vaccines may be lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Out of the 252 articles initially identified, 20 articles 8 14 15 18 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ( Tables 2 , 3 ) met the inclusion criteria and were selected for the systematic review. The flowchart representing the identification of the studies and inclusion/exclusion process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 252 articles initially identified, 20 articles 8 14 15 18 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 ( Tables 2 , 3 ) met the inclusion criteria and were selected for the systematic review. The flowchart representing the identification of the studies and inclusion/exclusion process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies were published between 2003 and 2017 and consisted of 4 original articles 14 15 27 29 and 16 case series 8 18 28 30 31 32 33 34 35 36 37 38 39 40 41 42 ( Table 2 ). They were carried out in fourteen different countries, particularly in Asia and Pacific regions (n=10), 15 27 28 29 31 33 34 35 37 41 Europe (n=7) 18 30 32 36 38 39 42 and North and South America (n=3). 8 14 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,27,28] Splenektomi immunizasyonu zayıflatma potansiyeline sahiptir ve bu hastalarda sepsis önemli bir sorundur. [29] Splenektomiyi takiben post-splenektomi sepsisten korunmak için pnömokok aşısı uygulanması önerilir. [30] Bu nedenle postsplenektomi enfeksiyonlarından korunmak amacıyla özellikle çocuklarda dalak koruyucu ameliyatlar tercih edilmesi önerilmektedir.…”
Section: Discussionunclassified
“…Some authors advocate complete splenectomy, reducing the possibility of recurrent disease and reducing postoperative bleeding, but most authors recommend a laparoscopic approach, especially for superficial, easily accessible cysts [14,15]. The justification for this attitude stems from the fact that the laparoscopic approach, compared to open surgery, is a minimally invasive procedure providing quick recovery while being safe and effective [16][17][18]. A statistically significant difference, in terms of postoperative complications and recurrence of the disease, has been evidenced by comparing the results of total splenectomy and organ-sparing surgical procedures.…”
Section: Discussionmentioning
confidence: 99%